The Effect of Differentiated Learning on Students’ Learning Outcomes in Pancasila Education: A True Experimental Study at SMAN 1 Badar - Rafi Anshari; Ruslan; Ridayaniruslan@usk.ac.id; Anggreni Bako (Jurnal Ragam Pengabdian, 2026)
The quality of education in Indonesia still faces challenges, particularly in learning practices that do not fully accommodate students’ diverse learning characteristics. In Pancasila Education, learning activities are often dominated by teacher-centered methods, which limit student participation and reduce the effectiveness of the learning process. This study aims to examine the effect of differentiated learning on students’ learning outcomes in Pancasila Education at SMA Negeri 1 Badar. The research employed a quantitative experimental approach using a pre-test and post-test control group design. The sample consisted of fifty students selected through simple random sampling and divided into two groups: an experimental group and a control group. Data were collected through learning outcome tests administered before and after the learning process. The data were analyzed using descriptive statistical analysis, simple regression analysis, and an independent sample comparison test to determine differences in learning outcomes between the two groups. The results show that students who experienced differentiated learning demonstrated higher improvement in learning outcomes compared to students who were taught using conventional learning methods. Differentiated learning provided opportunities for students to learn according to their readiness levels, interests, and learning profiles, which increased their participation and understanding of the learning material. The study concludes that differentiated learning has a positive effect on students’ learning outcomes in Pancasila Education and can create a more inclusive and student-centered learning environment